It’s Still About Race: Assessing Sources of Public Opinion on Immigration and Its Ties to Crime, Gangs, Drugs, and Border Control - Calvin Proffit; Leah Butler; Ben Feldmeyer (Crime & Delinquency, 2026)
There is a divide between political rhetoric and academic research on the topic of immigration and crime. Political rhetoric often claims that immigrants are dangerous and deportation is necessary to decrease crime. In contrast, empirical research demonstrates lower criminality among immigrants and little effect of deportation on crime. In light of these competing narratives, it is unclear where public perception stands on this issue. Some recent research has demonstrated that more American’s may be buying into political claims that immigration increases crime, however, recent research has not explored why the public has grown to accept these claims, and what factors drive these beliefs. To address these gaps, this study investigates the factors that are associated with endorsement of the four core pillars of contemporary political rhetoric concerning immigration’s effects on (1) crime, (2) gangs, (3) drugs, and (4) the need for immigration enforcement. Using a nationally benchmarked sample ( n = 1139) from Lucid Theorem collected in May–June 2025, the analysis assesses multiple theorized predictors of support for these narratives about immigration, including support for Trump, White nationalist sentiment, and Latino punitiveness, alongside other relevant correlates. The findings suggest Latino punitiveness is the strongest and most consistent predictor of these beliefs.